Control of the hermes II legged robot using basic stamp 2 [microfilm] - Ahmad Fadzlee H. A. Rashid (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Mekatronik)) - Universiti Teknologi Malaysia, 2002